Coping With Informality and Illegality: The Case of Street Entrepreneurs of Harare Metropolitan, Zimbabwe - Njaya, Tavonga (Asian Journal of Economic Modelling, 2014)
The study sought to examine how street vendors were coping with informality and illegality in metropolitan Harare. Data collection techniques included in-depth personal interviews, direct observations and documentary reviews. A semi-structured questionnaire was used to collect socio-economic and technical data pertaining to street vending and the resistance strategies adopted by the vendors. The study showed that despite numerous constraints placed on various groups of street traders, these groups had actually developed survival and resistance strategies that enabled them to maintain their livelihoods from public urban space. These strategies included “soft” forms of resistance; small-scale individual and group actions; subtle and innovative arrangements and even open protest and direct confrontation with the authorities. This was because for many street vendors, the street provided them with an honourable and respectable means of livelihoods. The study recommended that the government should recognise street industry through registration and introduction of a code of practice for street vendors. Over time a legal instrument should be introduced to regulate the operations of street traders. However, as a first step towards recognition, street vendors should constitute themselves into well organised associations that could become a forum of negotiations with the City of Harare. Future research should focus on quantifying the number of street vendors in Harare and their economic benefits.